D-aspartic acid: Biological role and potential applications as dietary supplement in sport - Ladyga, M.; Obminski, Z. (Medicina Sportiva, 2013)
Aspartic acid naturally occurs as an L- or D-form. Like many other chemical, aspartic acid demonstrates a varied biological activity dependent on which enantiomer it is in a pair. L-Aspartic acid (L-Asp) belongs to endogenous human amino acids involved in peptides and proteins formation which also partakes in purine and pyrimidine synthesis. D-Aspartic acid (D-Asp) occurs in organisms in a free form and does not create proteins. D-Asp plays an important role in the endocrine and the nervous system (functioning as a neurotransmitter and a neuromodulator). Involvement of D-Asp in the endocrine activity has also been widely analysed. Research into D-Asp role in the synthesis and release of sex hormones in humans have revealed that seminal plasma and spermatozoa contain D-Asp and that there is a direct correlation between D-Asp concentration and the quantity and motility of spermatozoa in semen. It was therefore hypothesized that D-Asp may play an exceptional role in spermatogenesis. These results have prompted the sports market to launch dietary supplements containing D-Asp that is recommended as a compound that enhances testosterone synthesis. The aim of this overview was to present current knowledge about the role of D-Asp in the nervous and endocrine system of animals, especially of humans, and find the answer to the question, could the D-Asp intake be beneficial for professional athletes.